Anion-active polyurethanes with increased content of renewable raw materials - Travinskaya, Т.V.; Brykova, А.N.; Savelyev, Yu.V.; Lebedev, E.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
Anionic polyurethanes (APU) degradable under environmental conditions have been synthesized on the basis of modified reactive oligomers produced by the glycerolysis reaction of palm (PO) and soybean (SO) oils without the use of harmful reagents, as well as natural castor oil (CO) and exopolysaccharide Xanthan (Xa). The mass fraction of natural components in synthesized polyurethanes amounts 70 %. The relationship between the component composition of Xa-containing polyurethanes on the basis of different vegetable oils and colloi dalchemical properties of dispersions, physico-mechanical and thermal properties of the films, and their ability to the degradation have been investigated.